Muntazam dalgaların sabit yatay iki paralel plakadan transmisyonu - Toraman, Fügen A. (Fen Bilimleri Enstitüsü, 1977)
Bu tezde yüzey yapıları ile muntazam dalgaların sö- nümlendirilmesi problemi incelenmektedir.Dalgalara sönümlen diren yüzey yapısı olarak sabit, yatay iki plâka düşünülmüş tür. Derinliği fazla olan denizlerde masif ve ağır yapıların inşaı zor olduğu gibi maliyetleri de yüksektir. Bu se beplerle son zamanlarda ağırlık yapılarına göre maliyetleri çok düşük ve inşaı kolay olan yüzey yapıları ile sakin suların elde edilmesine çalışılmaktadır. Bu çalışmada bu tür problemlere bir çözüm getirebilmeyi amaçlamaktadır. Bu tezde izlenen program aşağıdaki gibi özetlenmiş tir. Birinci bölümde incelenecek problem açıklanarak bu tür çalışmaların kısa bir tarihçesi verilmektedir. İkinci bölümde, bu tezde sıkışmayan ve sürtünmesiz akışkan içerisinde hareket eden küçük genlikli' muntazam dalgalar göz önüne alındığı için lineer dalga teorisi ele alınmaktadır. Ayrıca dalgaların süperpozisyonundan da bahse dilmektedir. Dalgaların genel bir sınıflandırılması da yapılmış tır. Bu sınıflandırma derinliğin dalga boyuna oranı (d/L) ile tariflenen rölatif derinliğe, dalgaları oluşturan kuvvetlere, mertebesine ve formlarına göre yapılmaktadır. Bu çalışmada VI dalgayı oluşturan kuvvetin sadece ağırlık kuvveti olduğu ve gelen dalgaların yayılan dalga olup sığ sularda yayıldığı kabul edilmiştir.Bu sebeple Stoker (1957) tarafından veri len Lineer Sığ Su Dalga Teorisinden de bahsedilmektedir. Üçüncü bölümde yapıların dalgalar üzerindeki etkilerinden bahsedilmekte ve bu konuda bir literatür çalışması verilmektedir. Sahil yapıları başlıca üç grupta toplanmıştır ağırlık yapıları, rijit ve yüzen cisimler, pnömatik ve hid rolik dalgakıranlar. Dördüncü bölümde, bu çalışmada incelenen probleme benzer olan daha önce yapılmış çalışmalar incelenmiştir. Problemin fiziksel görünümü de açıklanmaya çalışılmış ve olayın deneysel olarak incelenebilmesi için boyut analizi ile bazı boyutsuz parametreler tariflenmiştir. Buna göre olay aşağıdaki boyutsuz parametrelere bağlıdır. HTT H_.T CT, CR=f(Hr/L., d/L,A/L, e/Hj, g ~j~, g ~- ) Plâkalar arasındaki sürtünme kayıplarının olay üzerindeki etkisi sistemin enerji dengesi yazılarak araştırılmış ve böyle bir yaklaşımın gerçeği yansıtmadığı görülmüş tür. Ayrıca sabit, yatay iki plâka ile dolu gövdeli batmış cisimlerin mukayesesi yapılmıştır. Beşinci bölümde deney düzeneğinden "ve deneyler süresince kullanılan ölçüm sisteminden bahsedilmektedir. VII Altıncı bölümde deneysel olarak yapılan çalışmalar özetlenerek sonuçlar değerlendirilmektedir. a) Plâkaların ortalama su seviyesine göre konumlarının transmisyon olayı üzerindeki etkisi incelenmektedir. Burada e plâkalar arasındaki mesafeyi, H gelen dalga genliğini, R_ transmisyon dalgası genliğini, L dalga boyunu, d su derinliğini ifade ettiğine göre e/H». < 0.50 aralığında yapılan bütün deneyler Û.S.S.'nin üst plâka seviyesinde olması halinin elverişli olduğunu göstermektedir. Pratikte böy le bir yapının inşaı halinde G.S.S. üst plâka seviyesinde (ÜPS) olması tavsiye olunur. b) lolatif derinlik olarak tariflenen d /L. parametresi nm de olay üzer indeki etkisi incelenmiştir. Bu inceleme Macagno (.1954) 'nun çalışmasına benzer olarak, C= C_,(d/L, >,/d) değişimi bu çalışmada göz önüne alınan A/d ~ 1.0 değerine göre parametrik olarak incelenmiştir. Deney sonuçları d/L rölatif derinliği arttıkça CT transmisyon katsayısının azaldığını göstermektedir. c) Plâka boyundaki artışın transmisyon olayı üzerin deki etkisi incelenerek şu sonuçlara varılmaktadır. e, ) e/w < 0. 50 olması halinde H /L dalga dikliği art tıkça plâka boyundaki artışın transmisyon olayı Üzerindeki etkisinin arttığı izlenmektedir. c ).A/L oranının Ö.4Ö değerinden büyük olduğu haller de H/L dalga dikliğinin bu çalışmada göz önüne alınan bütün değişim aralıklarında transmisyon katsayısı A/L rölatif plâka boyunun fonksiyonu olmamaktadır. VIII d) Plâkalar arasındaki e açıklığının da olay üzerinde ki etkisi incelenmiştir. e açıklığı H gelen dalga genliğinin 1/2 ve 1/4'üne eşit tutulmaktadır. Buradaki amaç plâkalar civarında yörüngesel hareketi bozmak veya daha sınırlı bir hale getirmektir. Deneyler sonucu e'nin H /4 olması halinde daha küçük transmisyon değerlerinin elde edildiğini göster mektedir. e) Ayrıca H /L dalga dikliğinin olay üzerindeki etkisi araştırılmıştır. Bu incelemede aşağıdaki sonuçlar elde edilmektedir. e,) C - f (A/L, H /L) değişimi, bu çalışmada göz önüne alının HT/L değerlerine göre parametrik olarak gösterildiğinde deney sonuçlarından elde edilen en gayrimüsait eğrilerin hepsinin A/L~^ 0.20 değerinden geçtiği görülmektedir. e ) A/L rölatif plaka boyunun 0.10-0.20 aralığında olması halinde en az transmisyon. ''-H /L= 0.000-0.025 aralığın da izlenmekte, en yüksek transmisyon ise H/L= 0.051-0.075 aralığında görülmektedir. e ) A/L rölatif plâka boyunun 0.20 'der büyük olduğu hallerde ise en düşük transmisyon H/L-Ö. 051-0. 075 aralığında izlenmektedir.

This thesis deals with the problem of absorption of regular waves through surface structures. The particular sur face structure considered to consists of two fixed horizantal parallel plates. Cost of massive structures in deep water environment is considerably high, while their construction appears to be troublesome. Whereas a structure like the one investigated in this study rules out the above mentioned tendencies concerning with massive structures. Transmission of waves through a surface structure is dependent upon the characteristics of waves and of surface structure ; these characteristics being the water depth, the pe riod and amplitude of waves,, the relative position of plates to mean water level, the distance between the plates and the length of plates. The fact that the number of parameters involved is largeand this makes the problem difficult. In chapter 1. ; a) The main problem dealed in this thesis is. investi gated. b) Information is given on the history of these types of studies and types of surface structures considered by vari ous investigators. In chapter 2. ; since the regular waves of small ampli tudes in an incompressible inviscid fluid can be analysed with the aid of "Linear wave theory", the linear theory for incom- presible inviscid fluid is recapitulated. a) The Bernoulli equation is derived for the lineer wave theory. b) The expressions for the quantities; the velocity potential, the surface profile, the pressure distribution over a cross section and the wave energy are also derived. c) The chapter 2 includes also information on the su perposition of waves having different characteristic which are in motion either in the same direction or in the opposite direction. d) Taking into consideration the parameter d/L (the te_ lative water depth), waves are classified as shallow water depth and deep water depth. This classification has considerable ad vantages in studying wave problems through the linear theory. Waves are also classified taking into account their forms and the forces involved; the former being progressive waves, stan ding waves and solitary waves etc. and the latter being gravity waves, capillary waves and tidal waves. Due to the fact that the type of the waves investigated in this study is a gravity wave, expressions are given for the following.quantities; the velocity potential, the surface profile, the velocity vector, the displacementof fluid particle from some mean position, the pressure distribution over a cross section and the wave energy. e) The type of incident waves in the present study is also considered to be a progressive wave in shallow water, XI lineer shallow water theory developed by Stoker is also inclu ded in Chapter 2. In Chapter 3, effects of structures upon the waves are described and a short review is presented. Shore structu res are divided into three main groups : gravity structures, fixed and floating structures and phenomatic and hydraulic structures. In Chapter 4, earlier studies, which are relavent to the present problem, are presented in some detail. On the other hand, the problem is tried to solve by lineer theory and is shown that the present problem can not solved by linear. theory. Comparison between the problem of the fixed parallel horizontal plates and that of immersed solid structure (both having the same thickness) indicates that ; a) The former is more efficient than. the latter in the case when e/d-s 0,15 (e being the distance between the pla tes or the immersed depth, d the water depth), b) When e/d > 0.25, the latter is more efficient. In the case when 0.15 < e/d < 0.25, both gives the some transmis sion. In order to estimate the.friction losses through the plates, the energy balance of the system is emplo.yed. This shows this estiraetion is not sufficient. On dimensional grounds, the relevant quantities transmission coefficient C_ and reflection coefficient C_ are I K expressed in terms of nondimensional quantities as in the fol lowing ; CT,CR-:f(HI/L,d/!L, kfh, e/Hr g-^p-,g-^2 4.6.4 Re, /T, 2 1/Fr XII 2 Due to the fact that the effect of Reynolds and 1/Fr upon the transmission is negligehle these parameters are drop ped from the above expression. In Chapter 5., the experimantal set-up is introduced. This chapter consists of ; a) Brief review on wave generators, filters and absorbers b) Detailed information on the wave generator employed in the present study and, c) Some further information on the experimental set-up. In Chapter 6, the experiments done in this study are presented and the experimental results are analysed. This is summerized in the following. a) The effect of the position of the plates relative to the mean water level upon the transmission phenomenan.The plate position considered in this study are ; 1) The mean water level (MWL) coincides with the upper plates; 2) The MWL is. half a way from both the plates and, 3) The MWL coincides with the lcwer plates. For the e/H < 0.50, the plate positions except that the MWL coincides with the upper plate appear to have a negligible influence upon the transmission coefficient. b) The effect of relative water depth d/L on the trans mission phenomenon is that the transmission coefficient decre ases as the relative water depth increases. c) The effect of the plate length uppon the transmis sion. The results obtained are as follows : 1) When e/H < 0.50, XIII as wave steepness incresses, an increse in plate length makes an appreciable effect upon the transmission. 2) When X/L > 0.40 also for. the whole range of H/L considered in this study, X/L appears to be independent of the plate length. d) The effect of the gap, e, between the plates upon 1-1 the transmission. The gap, e, was kept ?=- H rH, H being the amplitude of coming wave. The objective in keeping the gap as specified above is to prevent the trajectory motion from occuring, or at least, to suppress it. In the experiments relatively smaller trans mission values were obtained in the case of e = -r HT. 4 I e.) The effect of wave steepness upon the transmission. 1) When C is analysed as a function of X/L and H/L the most unfavourable curves obtained from the experiments appear to intersect. On the point X/L = 0.20. 2) For 0.10 X/L = 0.20 minimum transmission was observed when H/L - 0.000-0.0025 and the highest transmission was observed, when H_/L= 0.051-0.075. 3) For X/L >0.20 minimum transmission was observed when H;i/L= 0.051-0.075.
Transmission of regular waves through two fixed horizontal parallel plates
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1977
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1977
Keywords: Dalga mekaniği; Dalgalar; Dalga hareketi kuramı; Wave mechanics; Waves; Theory of wave-motion